Environmental Protection and Stewardship of Subglacial Aquatic Environments - Doran, Peter T.; Vincent, Warwick F. (LSU Scholarly Repository, 2013)
Â© 2011 by the American Geophysical Union. All rights reserved. Environmental stewardship is a guiding principle of the Antarctic Treaty System. Efforts began in the 1990s to generate specific guidelines for stewardship of many terrestrial environments, including surface lakes and rivers. The relatively recent documentation of widespread subglacial aquatic environments, and planning for acquiring samples from them, has generated a need for stewardship guidelines for these environments. In response to a request from the U.S. National Science Foundation, the National Research Council of the National Academies of Sciences (NAS) created the Committee on the Principles of Environmental and Scientific Stewardship for the Exploration and Study of Subglacial Environments. The committee made 13 recommendations and a decision tree as a framework and flow chart for environmental management decisions. The committee report was also largely the basis of a Code of Conduct (CoC) for the exploration of subglacial environments formulated by a Scientific Committee on Antarctic Research Action Group. Both the NAS report and CoC have been used as guidance, to varying degrees, by subglacial research currently in progress.